The Evolution of Cybercrime and Its Impact on Various Sectors - Aprilia, Cindy; Gebrewold, Robel Amare; Bamiduro, Mercy Damilola; Borisova, Niurguiana; Mengdigali, Anel (Talenta Publisher, 2026)
This research undertakes an investigation, into the development of cybercrime and its significant consequences in five crucial industries; Manufacturing, Finance and Insurance, Professional Business and Consumer Services, Energy and Retail and Wholesale. By examining the progression of cybercrime, the study traces its evolution from curious hacking to its present state as a sophisticated global threat. The analysis delves into cyber incidents in these industries exploring how these criminal activities have evolved from simple digital pranks to globally impactful actions. The narrative provides insights into the effects of these crimes and the evolving strategies employed to mitigate risks enhancing our understanding of the ever-changing cybersecurity landscape. This research serves as an introduction to facilitate an exploration laying the foundation for an understanding of past current and emerging trends in cybercrime, within these key sectors. It aims to significantly contribute to the development and strengthening of future cybersecurity approaches and resilience by providing a deep understanding of these trends.